Representasi Pendidikan dalam Film Indonesia Kontemporer - Sifa, Afi Layyinus; Najiullah, Rizkiyah Gustiana (Tadabbur: Jurnal Integrasi Keilmuan, 2024)
This study aims to explain the representation of education in contemporary Indonesian films and its impact on education and learning among students. The method in this study uses descriptive analysis, namely analyzing case studies of the films "Laskar Pelangi," "Ada Apa dengan Cinta?", "Keluarga Cemara," and "Sang Pencerah". This study identifies key themes related to education, including the spirit of learning, educational injustice, the importance of family support, and educational reform. Through this representation, the films are able to increase social and cultural awareness, develop media literacy, teach moral and ethical values, and encourage creativity and historical understanding among students. This study found that contemporary Indonesian films have a positive impact on quality education and effective learning. Therefore, the integration of films into the education curriculum can be a useful strategy in improving the quality of learning in Indonesia.